FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN ALAT KONTRASEPSI SUNTIK DI WILAYAH KERJA PUSKESMAS BARA-BARAYA KECAMATAN MAKASSAR KOTA MAKASSAR - rosita rosita; Alia Andriany; Salli Desi (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2020)
Government program in spacing pregnancies with family planning programs. Injectable contraception is a method of contraception that is in great demand by mothers. Injectable contraceptives have side effects with each use. The purpose of this study was to determine the factors associated with the use of injecting contraceptives in the working area of ??the Bara-Baraya Public Health Center, Makassar District, Makassar City. The study used the case control study method with 48 respondents with the following distribution for the case group of 24 respondents and the control group of 24 respondents. The sample technique used was Simple Random Sampling. Based on the results of bivariate analysis using the Chi-Square test, it was found that factors related to the use of injecting contraceptives were the type of use with a p-value of 0.000, the time of use with a p-value of 0.003, knowledge with a p-value of 0.016, side effects of using contraceptives with a p-value of 0.024. Factors related to the use of contraceptives are good knowledge, type of use, duration of use and side effects. For mothers who use injectable contraceptives, they must anticipate the side effects of injecting contraceptives